(3QSGdI aj Cf dG eNGag aj GdehJs ((3GdSeGhi s)
(3ChdgG (B:s
(3deG cGf CYXe eG jdMb GdEfSGf ef GdNha ef GdehJ s
(3BNQgG (B:s
(3hdc Cf GdfGbU EPG NGa s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3HgG WeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdadSaI hGdefWbs